Long-term remission and survival in patients with relapsed or refractory multiple myeloma after treatment with LCAR-B38M CAR T cells: 5-year follow-up of the LEGEND-2 trial - Jie Xu; Bai-Yan Wang; Shan-He Yu; Shi-Jun Chen; Shuang-Shuang Yang; Rui Liu; Li-Juan Chen; Jian Hou; Zhu Chen; Wan-Hong Zhao; Ai-Li He; Jian-Qing Mi; et al. (Journal of Hematology & Oncology, 2024)
Abstract Background The autologous anti–B-cell maturation antigen (BCMA) chimeric antigen receptor (CAR) T-cell therapy LCAR-B38M has been approved for the treatment of relapsed and refractory multiple myeloma in many countries across the world under the name ciltacabtagene autoleucel. LEGEND-2 was the first-in-human trial of LCAR-B38M and yielded deep and durable therapeutic responses. Here, we reported the outcomes in LEGEND-2 after a minimal 5-year follow-up. Methods Participants received an average dose of 0.5 × 106 cells/kg LCAR-B38M in split or single unfractionated infusions after cyclophosphamide-based lymphodepletion therapy. Investigator-assessed response, survival, safety and pharmacokinetics were evaluated. Results Seventy-four participants enrolled and had a median follow-up of 65.4 months. The 5-year progression-free survival (PFS) and overall survival (OS) rates were 21.0% and 49.1%, with progressive flattening of the survival curves over time. Patients with complete response (CR) had longer PFS and OS, with 5-year rates of 28.4% and 65.7%, respectively. Twelve patients (16.2%) remained relapse-free irrespective of baseline high-risk cytogenetic abnormality and all had normal humoral immunity reconstituted. An ongoing CR closely correlated with several prognostic baseline indices including favorable performance status, immunoglobulin G subtype, and absence of extramedullary disease, as well as a combination cyclophosphamide and fludarabine preconditioning strategy. Sixty-two (83.8%) suffered progressive disease (PD) and/or death; however, 61.1% of PD patients could well respond to subsequent therapies, among which, the proteasome inhibitor-based regimens benefited the most. Concerning the safety, hematologic and hepatic function recovery were not significantly different between non-PD and PD/Death groups. A low rate of second primary malignancy (5.4%) and no severe virus infection were observed. The patients who tested positive for COVID-19 merely presented self-limiting symptoms. In addition, a sustainable CAR T population of one case with persistent remission was delineated, which was enriched with indolently proliferative and lowly cytotoxic CD4/CD8 double-negative functional T lymphocytes. Conclusions These data, representing the longest follow-up of BCMA-redirected CAR T-cell therapy to date, demonstrate long-term remission and survival with LCAR-B38M for advanced myeloma. Trial registration LEGEND-2 was registered under the trial numbers NCT03090659, ChiCTRONH-17012285.